182W and HSE constraints from 2.7 Ga komatiites on the heterogeneous nature of the Archean mantle. (1st May 2018) - Puchtel, Igor S.; Blichert-Toft, Janne; Touboul, Mathieu; Walker, Richard J.
Abstract: While the isotopically heterogeneous nature of the terrestrial mantle has long been established, the origin, scale, and longevity of the heterogeneities for different elements and isotopic systems are still debated. Here, we report Nd, Hf, W, and Os isotopic and highly siderophile element (HSE) abundance data for the Boston Creek komatiitic basalt lava flow (BCF) in the 2.7 Ga Abitibi greenstone belt, Canada. This lava flow is characterized by strong depletions in Al and heavy rare earth elements (REE), enrichments in light REE, and initial ε 143 Nd = +2.5 ± 0.2 and intial ε 176 Hf = +4.2 ± 0.9 indicative of derivation from a deep mantle source with time-integrated suprachondritic Sm/Nd and Lu/Hf ratios. The data plot on the terrestrial Nd-Hf array suggesting minimal involvement of early magma ocean processes in the fractionation of lithophile trace elements in the mantle source. This conclusion is supported by a mean μ 142 Nd = −3.8 ± 2.8 that is unresolvable from terrestrial standards. By contrast, the BCF exhibits a positive 182 W anomaly (μ 182 W = +11.7 ± 4.5), yet is characterized by chondritic initial γ 187 Os = +0.1 ± 0.3 and low inferred source HSE abundances (35 ± 5% of those estimated for the present-day Bulk Silicate Earth, BSE). Collectively, these characteristics are unique among Archean komatiite systems studied so far. The deficit in the HSE, coupled with the chondritic Os isotopic composition, but a positive 182 W anomaly, are best explained by derivation of the parental BCF magma from a mantle domain characterized by a predominance of HSE-deficient, differentiated late accreted material. According to the model presented here, the mantle domain that gave rise to the BCF received only ∼35% of the present-day HSE complement in the BSE before becoming isolated from the rest of the convecting mantle until the time of komatiite emplacement at 2.72 Ga. These new data provide strong evidence for a highly heterogeneous Archean mantle in terms of absolute HSE abundances and W isotopic composition, and also indicate slow mixing, on a timescale of at least 1.8 billion years. Additionally, the data are consistent with a stagnant-lid plate tectonic regime in the Hadean and Archean, prior to the onset of modern-style plate tectonics.